The effect of plyometric training on lower body strength in preadolescent athletes - Branet, C.; Grigoroiu, C.; Netolitzchi, M.; Wesselly, T. (BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2021)
In athletics, strength plays a special role, given that its development is focused on improving the speed of movement. The main form of expressing strength in athletics is speed-strength (explosive strength, take-off), which is representative for sprinting, jumping and throwing. Specialised studies have revealed that one of the most effective training methods used to develop explosive strength, also called explosive power, is the training based on plyometric exercises, but studies regarding the use of this method for the prepubertal age segment in athletic training are scarce. The purpose of this research is to investigate the degree of improvement in explosive strength in preadolescent athletes with the help of weekly plyometric training as compared to the control group. The research was carried out at the School no. 190 between 20 February and 17 June 2017. In order to conduct the experimental research, 42 athlete subjects of both genders, aged 11 to 13 years, were investigated. The experimental group was made up of 20 athletes, members of the Municipal Sports Club in Bucharest. The control group included 22 athlete subjects of both genders, who were trained by other coaches. Both groups performed four training sessions per week for 17 weeks. Analysing the results of the experiment, we can conclude that plyometric workouts contribute to the development of lower body strength in preadolescent athletes.